Employee Competence, Tri Hita Karana, and Compensation: Their Impact on Fraud Awareness in LPD - Asmarajaya, I Kadek Andy; Oktarini, Luh Nik; Rahmayuni, Ni Putu Ariyaniati (Jurnal Ilmiah Manajemen & Bisnis, 2025)
This study aims to analyze the influence of employee competence, Tri Hita Karana culture, and compensation on operational fraud awareness at the Village Credit Institution (LPD). The importance of awareness of potential fraud in maintaining the integrity of indigenous-based financial institutions. The method used is a quantitative approach through a survey of 99 respondents, analyzed using multiple linear regression. The research instrument was a questionnaire designed based on theoretical indicators for each variable and tested for validity and reliability. Simultaneous testing showed that all three variables jointly influence fraud awareness (F = 10.987; p less than 0.001) with an Adjusted R-square of 0.234, explaining 23.4% of the variation in fraud awareness. Partially, Tri Hita Karana culture (beta = 0.286; p = 0.002) and compensation (beta = 0.270; p = 0.001) have a positive and significant effect, while employee competence (beta = 0.014; p = 0.884) is not significant. Before regression analysis, classical assumption tests were conducted, including normality, multicollinearity, heteroscedasticity, and autocorrelation, all of which were met. These findings indicate that cultural values and incentive systems are more dominant than individual technical abilities in increasing awareness of operational fraud. The practical implications emphasize the importance of a work culture based on local values and a fair and transparent compensation system. Academically, this study enriches the literature on fraud prevention through a holistic approach that integrates cultural, structural, and personal aspects in the context of traditional institutions such as LPD.